Plant litter chemistry controls coarse‐textured soil carbon dynamics. (29th October 2022) - Huys, Raoul; Poirier, Vincent; Bourget, Malo Y.; Roumet, Catherine; Hättenschwiler, Stephan; Fromin, Nathalie; Munson, Alison D.; Freschet, Grégoire T.
Abstract: As soils store more carbon (C) than the Earth's atmosphere and terrestrial biomass together, the balance between soil C uptake in the form of soil organic matter (SOC) and release as CO2 upon its decomposition is a critical determinant in the global C cycle regulating our planet's climate. Although plant litter is the predominant source of C fuelling both soil C build‐up and losses, the issue of how litter chemistry influences this balance remains unresolved. As a contribution to solving that issue, we traced the fate of C during near‐complete decomposition of 13 C‐labelled leaf and root litters from 12 plant species in a coarse‐textured soil. We separated the soil organic carbon into mineral‐associated organic matter (MAOM) and particulate organic matter (POM) pools, and investigated how 14 litter chemical traits affected novel SOC formation and native SOC mineralization (i.e. the priming effect) in these soil fractions. We observed an overall net increase in SOC due to the addition of litter, which was stronger for root than for leaf litters. The presumed stable MAOM‐C pool underwent both substantial stabilization and mineralization, whereas the presumably less stable POM‐C pool showed substantial stabilization and reduced mineralization. Overall, the initial increase in soil C mineralization was fully counterbalanced by a later decrease in native soil C mineralization. POM‐C formation as well as MAOM‐C formation and mineralization were positively related to the initial litter lignin concentration and negatively to that of the nitrogen leachates, whereas the opposite was observed for POM‐C mineralization. Synthesis . Our results highlight the importance of litter chemical traits for SOC formation, and stabilization, destabilization and mineralization. In our coarse‐textured soil, the amount of MAOM‐C did not change despite large C fluxes through this pool. The litter chemical traits that drove these processes differed from those frequently reported for fine‐textured soils far from mineral‐associated C saturation. To account for these discrepancies, we propose an integrative perspective in which litter quality and soil texture interactively control soil C fluxes by modulating several SOC stabilization and destabilization mechanisms. Irrespective, our results open new critical perspectives for managing soil C pools globally. Abstract : Our results highlight the importance of litter chemical traits for SOC formation, and stabilization, destabilization and mineralization. In our coarse‐textured soil, the amount of MAOM‐C did not change despite large C fluxes through this pool. The litter chemical traits that drove these processes differed from those frequently reported for fine‐textured soils far from mineral‐associated C saturation. To account for these discrepancies, we propose an integrative perspective in which litter quality and soil texture interactively control soil C fluxes by modulating several SOC stabilization and destabilization mechanisms. Irrespective, our results open new critical perspectives for managing soil C pools globally.